2018
DOI: 10.1002/ptr.6160
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB and AMPK/PI3K/Akt signaling pathways are involved in the protective effects of Platycodon grandiflorum saponins against acetaminophen‐induced acute hepatotoxicity in mice

Abstract: Acute liver injury (ALI) induced by acetaminophen (APAP) overdose is the most common cause of drug-induced liver injury. Saponins from Platycodon grandiflorum (PGSs) ameliorate alcohol-induced hepatotoxicity and enhance human lung carcinoma cell death via AMPK signaling pathway. However, whether PGS could protect from APAP-induced ALI through AMPK activation and its downstream signals is still poorly elucidated. This work investigated the protective effect and the underlying mechanisms of PGS against APAP-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 48 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…In addition, CCl4 exposure upregulated the expression level of toll-like receptor 4 (TLR4) [ 52 ]. Similarly, previous reports also confirmed that MAPKs as a large family of seine/threonine kinases can also largely mediate the inflammatory signaling from the cell surface to nucleus [ 53 , 54 ]. Therefore, in the present work, the analysis of AP-1 expression in TLR4-MAPKs signal pathway will easily understand the protective effect of maltol on CCl 4 induced liver injury.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, CCl4 exposure upregulated the expression level of toll-like receptor 4 (TLR4) [ 52 ]. Similarly, previous reports also confirmed that MAPKs as a large family of seine/threonine kinases can also largely mediate the inflammatory signaling from the cell surface to nucleus [ 53 , 54 ]. Therefore, in the present work, the analysis of AP-1 expression in TLR4-MAPKs signal pathway will easily understand the protective effect of maltol on CCl 4 induced liver injury.…”
Section: Discussionsupporting
confidence: 62%
“…Hoechst 33258 staining was performed by using 5-μm thick tissue sections, and this was performed as described above [ 53 ]. Briefly, we randomly selected four sections in each group, and they were rehydrated by xylene and aqueous alcohol solutions carefully, and then were washed by PBS three times before being stained by the dye.…”
Section: Methodsmentioning
confidence: 99%
“…Platycodon grandiflorum (PG) has been used as an oriental herbal medicine native to East Asia (Korea, China, and Japan). It has various beneficial effects such as anti-inflammatory [12] and antibacterial [13] activities, improvement of liver function [14], and enhancement of cognitive ability [15]. In particular, platycodin D and platycodin D3 as main active ingredients of PG have anti-inflammatory activities, as it was shown to mitigate the inflammatory response induced by lipopolysaccharides (LPS) in RAW 264.7 (a macrophage cell line) cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Liver disease is common and often life-threatening. 1 Carbon tetrachloride (CCl 4 ), 2 paracetamol 3 and lipopolysaccharide 4 may cause acute liver injury. The occurrence of liver injury may be related to viral infection, alcohol and drugs.…”
Section: Introductionmentioning
confidence: 99%